2019
DOI: 10.1101/555292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated CO2 induces age-dependent restoration of growth and metabolism in gibberellin-deficient plants

Abstract: Main conclusion The effect of elevated [CO2] on the growth of tomato plants with reduced GA content is influenced by developmental stage.The increase of carbon dioxide (CO2) in the atmosphere during the last decades has aroused interest in the function of this gas in the growth and development of plants. Despite the known association between elevated CO2 concentration ([CO2]) and plant growth, its effects in association with gibberellin (GA), plant hormone that regulates de major aspects of plant growth, are s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Gasparini et al. (2019) reported that elevated CO 2 could enhance growth in gibberellin deficient tomatoes where gibberellin is dispensable. Xylem‐borne ABA is reported to regulate stomatal aperture under drought where elevated CO 2 may change this basic mechanism of drought by delaying the stomatal response to soil drying in tomato plants (Li, Li, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gasparini et al. (2019) reported that elevated CO 2 could enhance growth in gibberellin deficient tomatoes where gibberellin is dispensable. Xylem‐borne ABA is reported to regulate stomatal aperture under drought where elevated CO 2 may change this basic mechanism of drought by delaying the stomatal response to soil drying in tomato plants (Li, Li, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%